Cryptochrome Is a Regulator of Synaptic Plasticity in the Visual System of Drosophila melanogaster - Damulewicz, Milena; Mazzotta, Gabriella M.; Sartori, Elena; Rosato, Ezio; Costa, Rodolfo; Pyza, Elzbieta M. (Frontiers in Molecular Neuroscience, 2017)
Drosophila Cryptochrome (CRY) is a blue light sensitive protein with a key role in circadian photoreception. A main feature of CRY is that light promotes an interaction with the circadian protein TIMELESS (TIM) resulting in their ubiquitination and degradation, a mechanism that contributes to the synchronization of the circadian clock to the environment. Moreover, CRY participates in non-circadian functions such as magnetoreception, modulation of neuronal firing, phototransduction and regulation of synaptic plasticity. In the present study we used co-immunoprecipitation, yeast two hybrid and in situ proximity ligation assay to show that CRY can physically associate with the presynaptic protein Bruchpilot (BRP) and that CRY-BRP complexes are located mainly in the visual system. Additionally, we present evidence that light-activated CRY may decrease BRP levels in photoreceptor termini in the distal lamina, probably targeting BRP for degradation.